La «scripta» du Chansonnier du roi (BnF, fr. 844): nouvelles données pour l’étude de la genèse du recueil et de ses sources (Carte Romanze, 2023)
The composition of the «Chansonnier du Roi» (Paris, BnF, fr. 844), one of the most prominent Trouvère manuscripts, is usually located in Artois, based on different yet questionable pieces of evidence going from its contents, to its stemmatic relationships, to its decoration. The thorough investigation of its copyists’ scripta has yielded useful elements in order to refute this hypothesis and to further knowledge of the chansonnier sources.